The effects of prism adaptation on daily life activities in patients with visuospatial neglect: a systematic review. Issue 4 (19th May 2018) - Champod, Anne Sophie; Frank, Rachel C.; Taylor, Kristina; Eskes, Gail A.
ABSTRACT: Studies that have investigated prism adaptation (PA) effects on symptoms of visuospatial neglect have primarily used neuropsychological tests as outcome measures. An important question that remains to be answered is whether PA effects translate into improvements in patients' daily life activities. In the present review, we examined systematically the evidence for the effect of PA treatment on daily life activities in patients with neglect. Two authors independently assessed the methodological quality of 25 intervention and 1 follow-up studies using validated scales. PA effects were evaluated for reading/writing, activities of daily living (ADL) direct tests, ADL questionnaires, and navigation tests. Studies were evaluated as being of excellent ( n  = 1), good ( n  = 12), fair ( n  = 10), or poor ( n  = 3) quality. Among the 26 articles, a total of 32 measurements showed significant PA effects (one measurement from a study of excellent quality, 17 from studies of good quality, 10 from studies of fair quality, four from studies of poor quality), whereas non-significant effects were found in 15 measurements (two from a study of excellent quality, three from studies of good quality, eight from studies of fair quality, two from studies of poor quality). There is some evidence suggesting that PA can improve daily functioning, particularly as measured by reading/writing and ADL direct tests. The impact of several variables on PA effects should be investigated further including sample heterogeneity and time since injury.